Total Joint Arthroplasty Is Associated With a Decreased Risk of Traumatic Falls: An Analysis of 499, 094 Cases. Issue 20 (15th October 2020) - Driesman, Adam; Paoli, Albit R.; Wiznia, Daniel H.; Oh, Cheongeun; Mahure, Siddharth A.; Long, William J.; Schwarzkopf, Ran
Abstract : Introduction: The rate of traumatic falls in the aging cohort is estimated to increase across the United States. We sought to determine whether patients with lower extremity osteoarthritis (OA) who underwent total joint arthroplasty (TJA) had a reduced risk of falling compared with those with OA who did not undergo TJA. Methods: The New York Statewide Planning and Research Cooperative System database was queried from 2000 to 2015 to identify 499, 094 cases with primary diagnosis of hip or knee OA. Patients were stratified into 4 cohorts: group 1 (hip OA with total hip arthroplasty [THA] [N = 168, 234]), group 2 (hip OA without THA [N = 22, 482]), group 3 (knee OA with total knee arthroplasty [TKA] [N = 275, 651]), and group 4 (knee OA without TKA [N = 32, 826]). Patients were followed up longitudinally to evaluate the long-term risks of subsequent traumatic falls. Cox proportional hazards models were conducted to examine the relationship between patients' demographics and clinical characteristics and the risk of subsequent traumatic falls and reported as hazard ratios (HRs) with 95% confidence intervals (95% CIs). Results: Nineteen thousand seven hundred seventeen patients with hip OA underwent 168, 234 primary THAs (88.2%), and 308, 477 patients with knee OA underwent 275, 651 primary TKAs (89.4%) during the period 2000 to 2015. Compared with patients without TJA, those who underwent TJA were at a decreased risk of falls (THA HR 0.56 [95% CI, 0.48 to 0.66]) and TKA HR 0.66 [95% CI, 0.57 to 0.76]). Compared with age 40 to 49 years, risk increases for ages 70 to 79 years (HR = 4.3, 95% CI: 2.8 to 6.6) and 80 years or older (HR = 5.5, 95% CI: 3.8 to 8.1). Conclusion: TJA is associated with a decreased risk of long-term traumatic falls in elderly patients with the primary diagnosis of hip or knee osteoarthritis. Level of Evidence: Level III Retrospective Case-control study